Genetic markers in CYP2C19 and CYP2B6 for prediction of cyclophosphamide's 4‐hydroxylation, efficacy and side effects in Chinese patients with systemic lupus erythematosus. (25th December 2015) - Shu, Wenying; Guan, Su; Yang, Xiuyan; Liang, Liuqin; Li, Jiali; Chen, Zhuojia; Zhang, Yu; Chen, Lingyan; Wang, Xueding; Huang, Min
Abstract : Aims: The aim of the study was to investigate the combined impact of genetic polymorphisms in key pharmacokinetic genes on plasma concentrations and clinical outcomes of cyclophosphamide (CPA) in Chinese patients with systemic lupus erythematosus (SLE). Methods: One hundred and eighty nine Chinese SLE patients treated with CPA induction therapy (200 mg, every other day) were recruited and adverse reactions were recorded. After 4 weeks induction therapy, 128 lupus nephritis (LN) patients continued to CPA maintenance therapy (200–600 mg week –1 ) for 6 months, and their clinical outcomes were recorded. Blood samples were collected for CYP2C19, CYP2B6, GST and PXR polymorphism analysis, as well as CPA and its active metabolite (4‐hydroxycyclophosphamide (4‐OH‐CPA)) plasma concentration determination. Results: Multiple linear regression analysis revealed that CYP2B6 ‐750 T > C ( P  < 0.001), −2320 T > C ( P  < 0.001), 15582C > T ( P  = 0.017), CYP2C19 *2 ( P  < 0.001) and PXR 66034 T > C ( P  = 0.028) accounted for 47% of the variation in 4‐OH‐CPA plasma concentration. Among these variants, CYP2B6 ‐750 T > C and CYP2C19 *2 were selected as the combination genetic marker because these two SNPs contributed the most to the inter‐individual variability in 4‐OH‐CPA concentration, accounting for 23.6% and 21.5% of the variation, respectively. Extensive metabolizers (EMs) ( CYP2B6 ‐750TT, CYP2C19 *1*1) had significantly higher median 4‐OH‐CPA plasma concentrations (34.8, 11.0 and 6.6 ng ml ‐1 for EMs, intermediate metabolizers (IMs) and poor metabolizers (PMs), P  < 0.0001), higher risks of leukocytopenia (OR = 7.538, 95% CI 2.951, 19.256, P  < 0.0001) and gastrointestinal toxicity (OR = 7.579, 95% CI 2.934, 19.578, P  < 0.0001), as well as shorter median time to achieve complete remission (13.2, 18.3 and 23.3 weeks for EMs, IMs and PMs, respectively, P  = 0.026) in LN patients than PMs ( CYP2B6 ‐750CC, CYP2C19 *2*2) and IMs. Conclusions: Our findings have indicated that genetic markers of drug metabolizing enzymes could predict the 4‐hydroxylation, adverse reactions and clinical efficacy of CPA. This is a necessary first step towards building clinical tools that will help assess clinical benefit and risk before undergoing CPA treatment in Chinese SLE patients.